Osteoma Temporal Bone - Rare Case - Sikarwar, V; Lavania, A; Saxena, R (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.1 Issue 1 (Jan-Jun 2011) 25-26 DOI: http://dx.doi.org/10.3126/njenthns.v2i1.6782